A non-affine micro-macro approach to strain-crystallizing rubber-like materials. (February 2018) - Rastak, Reza; Linder, Christian
Abstract: Crystallization can occur in rubber materials at large strains due to a phenomenon called strain-induced crystallization. We propose a multi-scale polymer network model to capture this process in rubber-like materials. At the microscopic scale, we present a chain formulation by studying the thermodynamic behavior of a polymer chain and its crystallization mechanism inside a stretching polymer network. The chain model accounts for the thermodynamics of crystallization and presents a rate-dependent evolution law for crystallization based on the gradient of the free energy with respect to the crystallinity variables to ensures the dissipation is always non-negative. The multiscale framework allows the anisotropic crystallization of rubber which has been observed experimentally. Two different approaches for formulating the orientational distribution of crystallinity are studied. In the first approach, the algorithm tracks the crystallization at a finite number of orientations. In contrast, the continuous distribution describes the crystallization for all polymer chain orientations and describes its evolution with only a few distribution parameters. To connect the deformation of the micro with that of the macro scale, our model combines the recently developed maximal advance path constraint with the principal of minimum average free energy, resulting in a non-affine deformation model for polymer chains. Various aspects of the proposed model are validated by existing experimental results, including the stress response, crystallinity evolution during loading and unloading, crystallinity distribution, and the rotation of the principal crystallization direction. As a case study, we simulate the formation of crystalline regions around a pre-existing notch in a 3D rubber block and we compare the results with experimental data.